Elevated Atmospheric Levels of Benzene and Benzene-Related Compounds from Unconventional Shale Extraction and Processing: Human Health Concern for Residential Communities - Alisa L. Rich; Helen T. Orimoloye (SAGE Publishing, 2016)
Background The advancement of natural gas (NG) extraction across the United States (U.S.) raises concern for potential exposure to hazardous air pollutants (HAPs). Benzene, a HAP and a primary chemical of concern due to its classification as a known human carcinogen, is present in petroleum-rich geologic formations and is formed during the combustion of bypass NG. It is a component in solvents, paraffin breakers, and fuels used in NG extraction and processing (E&P). Objectives The objectives of this study are to confirm the presence of benzene and benzene-related compounds (benzene[s]) in residential areas, where unconventional shale E&P is occurring, and to determine if benzene[s] exists in elevated atmospheric concentrations when compared to national background levels. Methods Ambient air sampling was conducted in six counties in the Dallas/Fort Worth Metroplex with passive samples collected in evacuated 6-L Summa canisters. Samples were analyzed by gas chromatography/mass spectrometry, with sampling performed at variable distances from the facility fence line. Results Elevated concentrations of benzene[s] in the atmosphere were identified when compared to U.S. Environmental Protection Agency's Urban Air Toxics Monitoring Program. The 24-hour benzene concentrations ranged from 0.6 parts per billion by volume (ppbv) to 592 ppbv, with 1-hour concentrations from 2.94 ppbv to 2,900.20 ppbv. Conclusion Benzene is a known human carcinogen capable of multisystem health effects. Exposure to benzene is correlated with bone marrow and blood-forming organ damage and immune system depression. Sensitive populations (children, pregnant women, elderly, immunocompromised) and occupational workers are at increased risk for adverse health effects from elevated atmospheric levels of benzene[s] in residential areas with unconventional shale E&P.